LEW Auto : getting the wheels turning - Saini, Yvonne; Townsend, Stephanie (London : Wits Business School, 2018)
The case invites the student to consider how a LEW auto a small electronic repair workshop can attract new businesses and grow after two years of stagnating customer numbers.
Originally Published InSaini, Y., & Townsend, S. (2018). LEW Auto: Getting the wheels turning. WBS-2017-6. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic industries -- Case studies; Electronic apparatus and appliances -- Maintenance and repair -- Case studies; Automobiles -- Electric equipment -- Maintenance and repair -- Case studies; Success in business -- Case studies; Small business -- Management -- Case studies; Marketing -- Management -- Case studies